Evaluation of Physicochemical and Biological Parameters on the Water Quality of ShilabatiRiver, West Bengal, India. Issue 1 (1st January 2021) - Roy, Misha; Shamim, Farzana; Chatterjee, Saibal
ABSTRACT: Anthropogenic activities affect the rivers and the entire basin in different dimensions. All the river basins including Ganga and Damodar are polluted from unplanned anthropogenic activities. This study is an attempt to access the quality of Shilabati River by computing water quality and pollution index using eleven parameters pH, COD, BOD, DO, TDS, Total Hardness, Total Alkalinity, Phosphate, Chloride, Nitrate, and Turbidity measured at eighteen different sites. The BOD and TC counts are found to be 2.45 mg/l and 9334 MPN/100 ml; which reveal that the river water falls under the moderately polluted category of Central Pollution Control Board. The high phosphate concentration suggests a heavy load of anthropogenic and industrial wastes and contributes to the rise in COD and BOD. The high phosphate concentrations also account for the eutrophic water. The physicochemical parameters fall mostly under the E category of Central Pollution Control Board. The Water Quality Index, Comprehensive Pollution Index, and Eutrophication index values show that the river water quality is poor and seriously polluted indicating that the water is not suitable for drinking, domestic purpose, and also for healthy survival of aquatic life and needs urgent management.